Principles of Auditing : An Introduction to International Standards on Auditing - Rick Hayes (Pearson Education Limited, 2024)
This text offers a structured approach to principles of auditing using International Standards on Auditing as its basis. Written by a team of influential professional auditors with a wealth of teaching experience this book provides a real world perspective on current auditing practices with coverage of cutting edge developments and techniques.